Learning school improvement through collaboration: An evidence-based model - James, Freddy (School of Education, UWI, St. Augustine, 2014)
This paper reports on a study that explored educational reform in the secondary sector in Trinidad and Tobago (TandT) by analysing the Ministry of Education's policy documents and examining perspectives on the impact of the current reform agenda from the point of view of practitioners: school supervisors, principals, and teachers. A qualitative interpretive research design was used, which employed a range of data collection methods including questionnaires, document analysis, and interviews. The paper argues that a different, more inclusive and participatory approach to leading context-specific school improvement is required for policy initiatives to be successful. An evidence-based model that takes this approach into consideration is proposed. The model, though premised on findings within the TandT context, can be applicable to other contexts.
Keywords: Educational reform; Secondary education; School improvement; Educational cooperation; Stakeholders; Educational models; Trinidad and Tobago